2011
DOI: 10.1007/s10905-011-9305-5
|View full text |Cite
|
Sign up to set email alerts
|

Parasites and Dung Beetles as Ecosystem Engineers in a Forest Ecosystem

Abstract: Dung beetles serve as the intermediate host for Streptopharagus pigmentatus, a nematode parasite that infects an old world primate, the Japanese Macaque (Macaca fuscata). This study compares the behaviors of infected and uninfected beetles in both transmission dynamics and the ecological role of the parasite. The results suggest that parasitism does not alter the beetle's use of shelter or choice of substrate on Yakushima Island, Japan. However, infected beetles consume significantly less feces. Dung beetles r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…This is similar to previous findings on infection and beetle nesting behaviour (Boze et al, 2012), as well as to a number of studies in other taxa that demonstrated altered intermediate host behaviour due to infection (Lafferty and Morris, 1996;Berdoy et al, 2000). The parasites recovered from those beetle samples were not identified, limiting our understanding of how different parasite species influence beetle behaviour and the epidemiological relevance of those observations.…”
Section: Tablesupporting
confidence: 87%
See 1 more Smart Citation
“…This is similar to previous findings on infection and beetle nesting behaviour (Boze et al, 2012), as well as to a number of studies in other taxa that demonstrated altered intermediate host behaviour due to infection (Lafferty and Morris, 1996;Berdoy et al, 2000). The parasites recovered from those beetle samples were not identified, limiting our understanding of how different parasite species influence beetle behaviour and the epidemiological relevance of those observations.…”
Section: Tablesupporting
confidence: 87%
“…First, does beetle infection status influence burial depth? Parasites commonly influence the behaviour of free-living species, including intermediate hosts (Holmes and Bethel, 1972), and recent evidence suggests that dung beetles infected with the swine nematode Physocephalus sexalatus dig shallower tunnels compared with uninfected individuals (Boze et al, 2012). Infection status may further interact with beetle sex to influence the role of species traits on faeces burial depth, given the oft-observed strong male bias in infection intensity across both vertebrate and invertebrate species (Córdoba-Aguilar and Munguía-Steyer, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Phenotypic alterations brought about by parasites in their hosts can have several consequences for ecosystems, e.g. by releasing the prey community from predation pressure (Sato et al, 2012) or by affecting the availability of trophic resources to plant and animal communities (Hernandez and Sukhdeo, 2008;Boze et al, 2012). However, although the influence of PIPAs on ecosystem functioning is widely acknowledged (Thomas et al, 1997;Hatcher et al, 2012), we do not know to what extent the ecological impact of a parasite is related to the number of phenotypic alterations it brings about in its host.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, these are most likely coprophagous beetles (Coleoptera) of the genera Aphodius, Onthophagus or Geotrupes (Machida et al 1978;Kudo et al 1996;Boze et al 2012).…”
Section: The Model Parasitesmentioning
confidence: 99%
“…For example, dung beetles are likely ecosystem engineers on the island of Yakushima where they transmit S. pigmentatus and G. pulchrum to Japanese macaques. These beetles sequester feces from the environment for growth and reproduction, and in the process perform an important detritivorous ecosystem function, but it has been demonstrated that nematode infection reduces their capacity to function maximally in this role (Boze et al 2012). Whether the same parasite, or any other for that matter, can exact similar modifications of the engineering functions of Japanese macaque and other primate definitive hosts remains an exciting, yet no doubt challenging, problem for future research.…”
Section: Putting the Ecology Back Into Primate Parasite Ecologymentioning
confidence: 99%